Estrategias y prácticas turística en una ciudad patrimonio de la Humanidad, Toledo - Zárate Martín, M. Antonio (Geographicalia, 2015)
The tourism is a present activity in Toledo from very early dates, arnong other reasons for the abundant references along the history on its cultural, monumental and landscape singularity The declaration of this city as "Historical Artistic Set" in 1940 and its qualification as "City Patrimony of the Humanity " in 1986 they have helped to spread furtherrnore his tourist image. At present, public and private actors promote tourist strategies that promote new products, among them those who look for the active participation of the visitors and those who go to the world of the company and of the business to overcom the traditional links of this activity with the history and the monuments. One treats as political tourist that they seek to establish a balance between the advaritages of the proxirnity to Madrid and the excessive dependence that this reality originates.